2021
DOI: 10.1038/s41598-021-94681-9
|View full text |Cite
|
Sign up to set email alerts
|

Funneliformis mosseae inoculation under water deficit stress improves the yield and phytochemical characteristics of thyme in intercropping with soybean

Abstract: Intercropping of medicinal plants/legumes along with bio-fertilizer application is a relatively new sustainable practice for improving the yield and secondary metabolites production. Here, a 2-years field experiment was performed to evaluate the effects of water deficit stress and arbuscular mycorrhizal fungi (AMF) application (as bio-fertilizer) on nutrients concentration, dry matter yield, essential oil quantity and quality of thyme in intercropping with soybean. Three irrigation levels, including (i) irriga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…The results indicated that drought stress decreased AMF colonization, which was attributed to the degeneration of population and soil microbial activities as well as decreasing spore germination, spore density, root exudates, and supply carbohydrates by the host plant [31]. Similarly, Amani Machiani et al [27] reported that the AMF colonization rate significantly reduced in drought stress conditions.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The results indicated that drought stress decreased AMF colonization, which was attributed to the degeneration of population and soil microbial activities as well as decreasing spore germination, spore density, root exudates, and supply carbohydrates by the host plant [31]. Similarly, Amani Machiani et al [27] reported that the AMF colonization rate significantly reduced in drought stress conditions.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the decrease in plant performance was due to the lower nutrient availability as a result of the drought impact on the mass flow of N and diffusion of P and K into the plant roots [33]. Similarly, Amani Machiani et al [27] reported that the thyme (Thymus vulgaris L.) DMY reduced with moderate and severe water scarcity due to the decrease in macro-and micro-nutrients uptake in drought conditions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, intercropping can increase resource use efficiency, including water and nutrients, improve soil fertility to meet plant nutrient requirements, alleviate pest and disease pressure, enhance system stability, and increase crop quantity and quality 17 . Furthermore, intercropping improves the activity of beneficial soil microbes, increasing the availability of micro- and macro-elements 8 , 18 , 19 . Studies have shown that intercropping systems are agronomically and economically viable when the intercropped species consume the resources differently.…”
Section: Introductionmentioning
confidence: 99%